(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
The study was conducted during the period of 2010-2012 in the experimental field of RIMSA-Troyan on light grey pseudopodsolic soil. The aim of study is to determine the efficiency of herbicides Stratos Ultra (100 g/l cycloxydim) and Pulsar 40 (40 g/l imazamox) and their use in seed production of birdsfoot trefoil. The highest efficiency against weeds showed the treatment of birdsfoot trefoil crops with herbicide Pulsar 40 at a dose of 1200 ml/ha, applied in the year of sowing at the phase of 2-4 leaf of birdsfoot trefoil. The herbicide treatment restricted the opportunity to increase the population density of weeds and led to increase in seed yield by 30.2%. The high seed production under treatment with that herbicide determined also the high values of the structured elements of seed production. In the treatment by herbicide Stratos Ultra high seed production was also realised, which exceeded the control by 8.7% at a dose of 1000 ml/ha and 11.7% at a dose of 2000 ml/ha.